A case of recurrent malignant hemangiopericytoma of the hard palate - Saeed Nezafati; Shirin Fattahi; Faranak Moradi Abbasabadi (Wolters Kluwer Medknow Publications, 2013)
Hemangiopericytoma is an aggressive vascular tumor with a high propensity for recurrence and metastasis. The tumor is extremely rare in the head and neck region. We present a case of hemangiopericytoma on the right side of the hard palate in a 28-year-old male patient, which recurred after 5 years. This report demonstrates the malignant nature of this neoplasm. Computed tomography scans revealed a mass on the right side of the hard palate, which extended into the nasal cavity. Microscopic features of malignant hemangiopericytomas have been described as ovoid or spindle shaped tumor cells surrounded by reticular fibers that proliferate around recognizable capillaries. The examination of resected recurrent tumor was consistent with hemimaxillectomy.